Przeżycie estetyczne w procesie poznawania dzieła literackiego w szkole = The aesthetic experience in the process of literary work study at school - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper constitutes the attempt to define the aesthetic experience, the aesthetic and ultra-aesthetic qualities in terms of the contemporary theories of culture as well as in terms of the theory of aesthetic experience, within the context of systematic theory of teaching and learning literature.
Keywords: estetyka; dzieło literackie; nauczanie